Epidemiological, clinical and imaging profile of Multiple Sclerosis - Làzaro Aurelio Vàzquez Gòmez; Carlos Hidalgo Mesa; Benita Mabel Beltrán González; Yunier Broche Pérez; Ana María Mederos Herrera (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2021)
Background: multiple sclerosis is a neurological, autoimmune, degenerative, chronic and progressive demyelinating disease associated with different genetic and environmental factors. Objective: to characterize epidemiologically, clinically and imaging patients with a diagnosis of multiple sclerosis. Methods: observational, descriptive, cross-sectional study on all patients with a diagnosis of multiple sclerosis with follow-up at the Arnaldo Milián Castro Provincial University Clinical-Surgical Hospital, in Villa Clara during the period from January 2014 to December 2019. The epidemiological variables analyzed: sex, age of disease onset, skin color, place of origin; clinical variables: symptoms at the beginning and at present; number of shoots; years of evolution, clinical forms; Imaging variables: number of lesions, location, atrophy or change in signal intensity of the corpus callosum and McDonald's criterion fulfilled. Results: there was a higher incidence of females with 80 patients. It was found that 59 patients had a relapsing-remitting clinical form, 21 patients had a secondary progressive form, 4 patients had a primary progressive and 2 patients had a relapsing progressive one. Symptoms: motor deficit, sensory deficit and cerebellar alterations were the most frequent at the beginning and at present. Disability evaluated as minimal was found in 50 patients and 31 patients had 2 to 4 lesions on nuclear magnetic resonance. Conclusions: Adequate epidemiological information on patients with multiple sclerosis in Villa Clara was obtained satisfactorily. It is important to consider this report as a basis for decision-making on issues of projection of treatment and care, aspects of great importance in high-cost diseases, such as multiple sclerosis.